YBX1 modulates humoral immunity through post-transcriptional regulation in B cells - Kunz, Viktoria; Bommert, Kathryn S.; Bargou, Ralf; Bommert, Kurt (Frontiers in Immunology, 2025)
IntroductionY-box binding protein 1 (YBX1) is a multifunctional RNA- and DNA-binding protein implicated in transcriptional regulation, mRNA stabilization, and translation, as well as cell proliferation and stress responses. Although widely studied in cancer and inflammation, its in vivo role in hematopoiesis and immune regulation remains incompletely understood.MethodsTo investigate YBX1 function in these contexts, we performed transplantation of fetal liver cells (FLCs) from E14.5 Ybx1-/- and Ybx1+/+ embryos (CD45.2) into lethally irradiated CD45.1 congenic recipients. Hematopoietic reconstitution, immune cell subsets, B cell receptor (BCR) signaling, and humoral responses were subsequently analyzed.ResultsDespite markedly reduced cellularity and progenitor frequencies in Ybx1-/- fetal livers, multilineage hematopoietic reconstitution was largely preserved. Analysis of immune cell subsets revealed functional alterations: Ybx1-/- myeloid-derived suppressor cells (MDSCs) displayed enhanced nitrite production associated with upregulated Nos2 expression while maintaining their immunosuppressive capacity. In the lymphoid compartment, Ybx1-/- B cells underwent normal maturation and proliferated in response to LPS and IL-4, but exhibited weakened BCR signaling, characterized by reduced calcium mobilization and diminished expression of key signaling proteins, including BLNK. Strikingly, humoral responses were compromised in Ybx1-/- FLC-reconstituted mice, with significantly reduced antigen-specific antibody production following both T cell-dependent and -independent immunizations.DiscussionMechanistic analyses demonstrated that YBX1 directly binds to immunoglobulin mRNAs and enhances their translation, establishing a post-transcriptional mechanism by which YBX1 supports humoral immunity. Together, these findings reveal an unexpected, non-redundant role for YBX1 in regulating immune effector functions. By enhancing immunoglobulin and myeloid inflammatory mediator mRNA translation, YBX1 emerges as a contributor to immune homeostasis and possibly tumor immune evasion by regulating the expression of immunomodulatory factors in immune and malignant cells alike.